A formative study exploring perceptions of physical activity and physical activity monitoring among children and young people with cystic fibrosis and health care professionals - James Shelley; Stuart J Fairclough; Zoe R Knowles; Kevin W Southern; Pamela McCormack; Ellen A Dawson; Lee E F Graves; Claire Hanlon (BMC Pediatrics, 2018)
Abstract Background Physical activity (PA) is associated with reduced hospitalisations and maintenance of lung function in patients with Cystic Fibrosis (CF). PA is therefore recommended as part of standard care. Despite this, there is no consensus for monitoring of PA and little is known about perceptions of PA monitoring among children and young people with CF. Therefore, the research aimed to explore patients’ perceptions of PA and the acceptability of using PA monitoring devices with children and young people with CF. Methods An action research approach was utilised, whereby findings from earlier research phases informed subsequent phases. Four phases were utilised, including patient interviews, PA monitoring, follow-up patient interviews and health care professional (HCP) interviews. Subsequently, an expert panel discussed the study to develop recommendations for practice and future research. Results Findings suggest that experiences of PA in children and young people with CF are largely comparable to their non-CF peers, with individuals engaging in a variety of activities. CF was not perceived as a barrier per se, although participants acknowledged that they could be limited by their symptoms. Maintenance of health emerged as a key facilitator, in some cases PA offered patients the opportunity to ‘normalise’ their condition. Participants reported enjoying wearing the monitoring devices and had good compliance. Wrist-worn devices and devices providing feedback were preferred. HCPs recognised the potential benefits of the devices in clinical practice. Recommendations based on these findings are that interventions to promote PA in children and young people with CF should be individualised and involve families to promote PA as part of an active lifestyle. Patients should receive support alongside the PA data obtained from monitoring devices. Conclusions PA monitoring devices appear to be an acceptable method for objective assessment of PA among children and young people with CF and their clinicians. Wrist-worn devices, which are unobtrusive and can display feedback, were perceived as most acceptable. By understanding the factors impacting PA, CF health professionals will be better placed to support patients and improve health outcomes.